Biodiversity and Health in the Face of Climate Change 2019
DOI: 10.1007/978-3-030-02318-8_10
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and Spiritual Well-being

Abstract: Among government agencies, practitioners and researchers there is growing interest in the potential of natural environments for human health and wellbeing. In parallel, conserving biodiversity is seen as critical in this effort. Likewise, spiritual well-being is increasingly considered as an important dimension of human health. This chapter examines the interrelationship between biodiversity and spiritual well-being. We first consider what spiritual well-being is. Then, based on a review of literature, we disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 115 publications
(128 reference statements)
0
18
0
1
Order By: Relevance
“…Specific woodland smells (e.g. ‘earthy’) also evoked feelings of peace and calmness, and participants often referred to a connection with nature or a transcendent other, falling within the theorised framework for how biodiversity relates to spiritual wellbeing (Irvine et al 2019 ). These findings align with those of Pálsdóttir et al ( 2021 ), who document how garden smells (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific woodland smells (e.g. ‘earthy’) also evoked feelings of peace and calmness, and participants often referred to a connection with nature or a transcendent other, falling within the theorised framework for how biodiversity relates to spiritual wellbeing (Irvine et al 2019 ). These findings align with those of Pálsdóttir et al ( 2021 ), who document how garden smells (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…weather). However, psychological wellbeing is also thought to encompass separate cognitive and emotional domains (Andrews and McKennell 1980 ), while an expanded version of the biopsychosocial model recognises a spiritual wellbeing domain (McKee and Chappel 1992; Linton et al 2016 ; Irvine et al 2019 ). As such, the ‘biopsychosocial-spiritual’ model of wellbeing may comprise physical (outcomes related to the physical body and how one feels physically), cognitive (influences on a person’s state of mind), emotional (refers to the presence of positive and negative emotions and mood), social (how an individual perceives their connections with others) and spiritual (involves the relationship with one’s self and in some cases feelings of being connected to something greater) domains (Irvine et al 2013 ; Linton et al 2016 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…36 Irvine et al, in a review of spirituality and biodiversity, offer that 'there is suggestive evidence that biodiversity appears to contribute to spiritual outcomes'. 37 They note that these sorts of observation are critical in making clearer links between conservation of biodiversity and human well-being.…”
Section: Nature and Well-beingmentioning
confidence: 99%
“…Transcendent experiences-such as humility, awe (strong emotions of amazement and wonder; Ballew and Omoto, 2018), and reflection (thinking about one's life, goals and priorities; Kaplan and Kaplan, 1989)-contribute to well-being (Davis and Gatersleben, 2013;Capaldi et al, 2015). Sights and sounds of nature, both mundane and awesome, have been found to elicit transcendental experiences (Capaldi et al, 2015;Irvine et al, 2019). Considering wilderness as a proxy for a biodiverse environment, studies have found that wilderness-based recreation can contribute to the ability to reflect about one's purpose and meaning in life, and the spiritual experiences of humility and awe (Irvine et al, 2019).…”
Section: Transcendent Experiences (Awe Humility Reflection)mentioning
confidence: 99%
“…Sights and sounds of nature, both mundane and awesome, have been found to elicit transcendental experiences (Capaldi et al, 2015;Irvine et al, 2019). Considering wilderness as a proxy for a biodiverse environment, studies have found that wilderness-based recreation can contribute to the ability to reflect about one's purpose and meaning in life, and the spiritual experiences of humility and awe (Irvine et al, 2019). Qualitative research has shown that viewing some types of wildlife can contribute to a sense of humility and awe (Curtin, 2009).…”
Section: Transcendent Experiences (Awe Humility Reflection)mentioning
confidence: 99%